Internalisasi nilai-nilai pendidikan Agama Islam untuk membentuk etika bermedia sosial dikalangan generasi Z - Ummi Faizah (Jurnal Pendidikan Agama Islam, 2026)
This study aims to identify social media ethical challenges among Generation Z and examine Islamic Religious Education (IRE) values as a normative framework for developing responsible digital character. Employing a qualitative library research approach, data were collected from books, journals, and academic documents, then analyzed using content analysis. Findings reveal that primary digital ethical challenges stem from a gap between technical proficiency and moral maturity, exacerbated by online disinhibition, echo chamber algorithms, and instant validation culture. IRE values such as ṣidq (honesty), amanah (trustworthiness), tabayyun (verification), and akhlaq al-karimah (noble character) prove highly relevant as a holistic foundation for cyber ethics. Effective internalization requires contextual integration within digital literacy, case-based learning, consistent role modeling, and collaborative ecosystems reinforced by digital muhasabah (self-reflection). Theoretically, these findings enrich contemporary Islamic education by affirming that digital character must be grounded in spiritual-moral values. Practically, this research provides conceptual and operational guidance for educators, families, and policymakers to optimize IRE’s role in shaping a Generation Z that is digitally competent, ethical, and morally upright in virtual spaces.